Aspartate aminotransferase/alanine aminotransferase ratio and subsequent cancer development. (1st December 2021) - Kobayashi, Daiki; Yamamoto, Kazuki; Kimura, Takeshi; Shimbo, Takuro
Abstract: Background: We aimed to evaluate the association between the aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio and subsequent development of any type of cancer in an apparently healthy population. Methods: We conducted a retrospective cohort study at St. Luke's International Hospital, Tokyo, Japan between 2005 and 2018. All participants who visited for voluntary health checkups were included. We divided the participants into different quintiles based on the baseline AST/ALT ratios and examined the outcomes. Results: A total of 85, 658 participants were included. The mean age was 44.7 years (standard deviation 12.0) at baseline, and 42, 913 (50.1%) of them were men. During a median follow‐up of 61.6 months, 4701 (5.5%) participants developed some type of cancer. Compared with the middle AST/ALT ratio group, no other groups had similar adjusted hazard ratios (HR) for the development of any type of cancer in both men and women. When stratified by alcohol consumption, very high (adjusted HR 1.36; 95% CI 1.13–1.63) and high (adjusted HR 1.26; 95% CI 1.05–1.50) AST/ALT ratio groups among men who were regular drinkers had increased adjusted HRs for any type of cancer development, but the very high AST/ALT ratio group among men who were abstainers (adjusted HR 0.64; 95% CI 0.42–0.97) and very low AST/ALT ratio group among men who were occasional drinkers (adjusted HR 0.69; 95% CI 0.48–0.98) had lower adjusted HRs compared with the middle AST/ALT ratio group. Among women, regardless of alcohol consumption, adjusted HR for any type of cancer development was similar across all AST/ALT ratio groups. Conclusion: People with higher AST/ALT ratios tended to have a higher risk of developing any type of cancer among men who were regular drinkers, but this risk was lower among men who were abstainers. Among women, regardless of alcohol consumption, there was no association between the development of any type of cancer and AST/ALT ratio. Abstract : People who had higher aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio tend to have a higher risk of developing any type of cancer compared with those with middle AST/ALT ratio, especially regular drinkers. Cancer development in the digestive organ, other than hepatocellular carcinoma; urinary tract; or respiratory and intrathoracic organs may be associated with AST/ALT ratio.